Study of lipids and lipoprotein levels in uncomplicated diabetes mellitus patients attending Shadan hospital - Tulla, Samatha; Siddiqua, Syeda Ayesha (International Journal of Research in Medical Sciences, 2021)
Background: Lipid and lipoprotein levels are interrelated with diabetes mellitus. Abnormalities in the levels of total cholesterol (TC) or triglycerides (TAG) or low-density lipoprotein (LDL) cholesterol or very-low-density lipoprotein (VLDL) cholesterol or high-density lipoprotein (HDL) cholesterol or lipoprotein (a) [Lp (a)] is traditionally named as dyslipidemia. Diabetes mellitus has been known to be associated with lipid disorders and cardiovascular diseases. In patients with diabetes mellitus, dyslipidemia occurs earlier in life, leading to increased morbidity and mortality rates. The study aims to assess the changes in lipids and lipoprotein levels in uncomplicated diabetes mellitus patients. Methods: A case-control type of study was conducted for 18 months (September 2011 to March 2013) at the Department of General Medicine, Shadan Hospital, Hyderabad. Ethical committee approval was taken before the study from the institutional ethical committee. A total of 120 subjects, 60 non-diabetic (healthy) control subjects with matching age and gender and, 60 cases of subjects with uncomplicated diabetes mellitus were enrolled based on predetermined inclusion and exclusion criteria. Results: This study was conducted to evaluate the changes in lipids and lipoprotein levels between control (normal and healthy subjects) and case (subjects with uncomplicated diabetes mellitus) groups. The Mean±SD levels of total cholesterol, triglycerides, low-density lipoprotein cholesterol, very-low-density lipoprotein cholesterol, and lipoprotein (a) were higher in the cases group and showed statistical significance when compared with the control group. Conclusions: Our study states that there are abnormal levels of lipids and lipoprotein in subjects with uncomplicated diabetes mellitus, which is the foremost cause of cardiovascular diseases, coronary heart disease, dyslipidemia, etc.